2014
DOI: 10.1108/cg-05-2012-0044
|View full text |Cite
|
Sign up to set email alerts
|

Board structure in listed firms: evidence from an emerging economy

Abstract: Purpose – This paper aims to understand the determinants of board structure of listed firms at institutional, industry and firm levels within an emerging economy. At the institutional level, the paper explores laws, managerial culture and the role of state in instituting and endorsing corporate governance practices. At the firm level, ownership patterns (family and non-family), experience in the capital markets, age and size of the firms are studied to find out the relation between these variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…requirements in terms of the size of the boards: the average number of directors is 8.5 in the Istanbul Stock Exchange's (I.S.E.) 50 index companies in 2010 (Arslantaş & Fındıklı, 2010) and 6 in listed non-financial firms in 2014 (Oba et al, 2014). Board size in Turkey seems to change based on the type of industry and ownership structure as well; for example, Selekler and Yıldırım (2009) found that, in the financial sector, the average number of directors in the boardroom is 8.5, but for the manufacturing and service sectors the number changes to 7.7 and 7.2, respectively.…”
Section: Board Characteristics In Turkeymentioning
confidence: 99%
See 2 more Smart Citations
“…requirements in terms of the size of the boards: the average number of directors is 8.5 in the Istanbul Stock Exchange's (I.S.E.) 50 index companies in 2010 (Arslantaş & Fındıklı, 2010) and 6 in listed non-financial firms in 2014 (Oba et al, 2014). Board size in Turkey seems to change based on the type of industry and ownership structure as well; for example, Selekler and Yıldırım (2009) found that, in the financial sector, the average number of directors in the boardroom is 8.5, but for the manufacturing and service sectors the number changes to 7.7 and 7.2, respectively.…”
Section: Board Characteristics In Turkeymentioning
confidence: 99%
“…mandates that at least one-third of all directors be independent members, a rule that is effective from 2012. Independent members make up 15% of the boardroom in family firms, but 13% for non-family firms, while a large majority of firms in 2010 (74%) did not have any independent directors on their boards (Oba et al, 2014). However, recent studies of listed companies have stated that the ratio of independent directors is progressing and had reached 28.8% by 2015 (Ararat, Alkan, & Aytekin, 2016).…”
Section: Board Characteristics In Turkeymentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from both developed and developing economies were mixed and inconclusive. Based on previous studies board Size was operationalized as the total numbers of board membership (Saha & Kabra, 2019;Oba, Tigrel, & Sener, 2014).…”
Section: 2empirical Review 221 Board Size and Firm Performancementioning
confidence: 99%
“…Turkey has a peculiar corporate governance system compared with its European and North American counterparts. Volatile and unreliable financial and capital markets, insufficient liquidity to provide external control, and weak legal protection for minority shareholders shapes external corporate governance environment in Turkey (Nilsson, 2007;Oba, Tiğrel, & Şener, 2014;Yamak & Ertuna, 2017). On the other hand, internal governance system in Turkey features the main characteristics of family-based systems.…”
Section: Environmental Determinants Of Managerial Discretionmentioning
confidence: 99%